Web-Based Tray Monitoring Application Using CodeIgniter (CI) Framework: Case Study of PT SIIX EMS Indonesia - Sidqi Awaludin; Agustia Hananto; Elfina Novalia (Bulletin of Network Engineer and Informatics, 2026)
PT SIIX EMS Indonesia is a manufacturing company that utilizes trays as a means for temporary storage and component distribution across its production lines. However, the monitoring and recording process for these trays is still conducted manually, leading to various issues such as recording errors, data loss, delays in information delivery, and difficulties in real-time tray tracking. These problems result in decreased operational efficiency and sub-optimal decision-making by management. Therefore, this study aims to design and develop a web-based tray monitoring information system to enhance the effectiveness of tray management within the company. The research methodology includes data collection techniques through direct observation and literature review. Meanwhile, the system development follows the Waterfall model, consisting of requirements analysis, system design, implementation, testing, and maintenance. The application was developed using the CodeIgniter framework with PHP programming language and MySQL as the database for data storage. The results indicate that the developed web-based tray monitoring system successfully integrates data for recycled trays, new trays, and scrap trays into a centralized system while providing a real-time monitoring dashboard. System testing using the Black Box Testing method shows that all application features function according to user requirements. Consequently, the developed system improves data recording accuracy, accelerates the information retrieval process, and assists management in making faster and more accurate decisions at PT SIIX EMS Indonesia.